A note on Prediction of the U.S. Population and Diabetic Population - Mulatu, Lemma,; Enye, B; Oh, H.; McBeth, E. (IJRDO -JOURNAL OF MATHEMATICS, 2019)
The world is home to over seven billion people, and more than twenty million animals. With seven continents, the population of the world is spread out in each country within the continents. One of the most populated countries in the world is the United States. It is ranked 3rd on the list of largest countries by population, and is home to over 300 million people. Figure 1, show the population of the United States from the 1980 to 2014, and those keep increasing every day. Although, the country is for its entertainment, scientific research, and multicultural diversity because people from all over the world move to have a better life, is also has the highest rate of diabetes on the list of developing countries. Figure 2, show the number of diabetics cases from 1980 to 2014. The data is based on age range (18 and higher), education (less than to greater then high school), gender, and race. Combining the different categories together, the data and graphical trend was created. Although the rate, is from 1980 to 2014, the goal of the research is to predict the population of the United States and the number of diabetic cases within that population for 2018 using Least Square Approximation Method.